2023
DOI: 10.1097/jsm.0000000000001140
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Personal and Injury-Related Factors Predicting Deficits in Quality of Life Domains Among Pediatric Athletes: Findings From the Sport Concussion Outcomes in Pediatrics Study

Abstract: Objective: To examine patient and injury factors that may predict quality of life (QoL) and symptom duration after concussion. Design: Prospective, longitudinal. Settings: Six children's hospital-based medical centers and 9 secondary school athletic training facilities. Patients: Pediatric patients (8-18 years) were enrolled as part of the Sport Concussion Outcomes in Pediatrics (SCOPE) study during their initial visit for a diagnosis of sport-related concussion. Interventions: Patients completed a medical his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Earlier studies have reported varying outcomes. While some reported that types and numbers of fractures have inverse relationships with the overall QoL,[ 27 33 ] others reported an association with the physical domain part of the QoL alone. [ 34 35 ] Sluys et al .…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have reported varying outcomes. While some reported that types and numbers of fractures have inverse relationships with the overall QoL,[ 27 33 ] others reported an association with the physical domain part of the QoL alone. [ 34 35 ] Sluys et al .…”
Section: Discussionmentioning
confidence: 99%